Marx, Engels and the philosophy of science - Bedford, David 1954-; Workman, W. Thom 1959- (Routledge, 2023)
"This book expounds the dialectical conception of science largely implicit in the writings of Marx and Engels, offering a sympathetic reconstruction of a philosophy of science commensurate with Marx's thought. Drawing on a reading of dialectics found in Plato and Hegel, it recasts Marx's implicit ontology in terms of dialectical conceptions of the world, as these conceptions have responded to the growing sophistication of modern science. It thus deepens our understanding of materialist philosophy as it relates to science and draws out Marx's logic of science in light of continuing discussions. As such, it will appeal to philosophers with interests in the nature and development of science, and Marxist thought"--
Keywords: Engels, Friedrich -- 1820-1895; Marx, Karl -- 1818-1883; Wissenschaftsphilosophie; Communism and science; Science / Philosophy; Historical materialism; Marx, Karl / 1818-1883 / Philosophy; Engels, Friedrich / 1820-1895 / Philosophy; Engels, Friedrich / 1820-1895; Marx, Karl / 1818-1883